2015
DOI: 10.1007/s11104-015-2618-y
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community shifts 2.6 years after top dressing of Miscanthus biochar, hydrochar and feedstock on a temperate grassland site

Abstract: Background and aims Within the last decades, consid-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…However, since this earlier publication, no new evidence for such effects can be cited. Several authors (Lehmann et al , ; Joseph et al , ; Rex et al , ; Kolton et al , ; Ye et al , ) recently showed that biochar application (iv) influences the rhizosphere microbiome, may increase microbial diversity or metabolic efficiency and that it can cause changes in the metabolic potential of the rhizosphere. Enriching biochar with microbial nutrients such as cow urine may further modify and probably increase the influence on the rhizosphere microbiome and microbial‐root symbioses.…”
Section: Discussionmentioning
confidence: 99%
“…However, since this earlier publication, no new evidence for such effects can be cited. Several authors (Lehmann et al , ; Joseph et al , ; Rex et al , ; Kolton et al , ; Ye et al , ) recently showed that biochar application (iv) influences the rhizosphere microbiome, may increase microbial diversity or metabolic efficiency and that it can cause changes in the metabolic potential of the rhizosphere. Enriching biochar with microbial nutrients such as cow urine may further modify and probably increase the influence on the rhizosphere microbiome and microbial‐root symbioses.…”
Section: Discussionmentioning
confidence: 99%
“…The number of published works on the impact of HC on soil-resident fungi is very limited and undoubtedly lower than that of BC on the same topic. Microbial community shift, including fungal species (Rex et al., 2015) and performance of arbuscular mycorrhizal fungi (Salem et al., 2013) in the presence of HC were the only two aspects addressed by scientists to date. Recent findings indicate that changes in the functionality of microbial community may occur as a consequence of BC and HC application to soil, and such changes would eventually have also a relevant impact on soil fertility, especially when ligninolytic fungi are involved.…”
Section: Introductionmentioning
confidence: 99%
“…The adding of "fresh biochar" to soil has been shown to induce short-term disturbance to the moisture equilibrium in soils due to the effect of capillary action, drawing moisture from soil pore spaces. In turn, this can cause negative effects on soil microbial communities and abundance through instantaneous desiccation (Dempster et al, 2012;Ameloot et al, 2013;Rex et al, 2015). However, soil pH and the other targeted traits were not significantly correlated with any bacterial diversity index.…”
Section: Influence Of Soil Chemical Properties On the Diversity Of Rhmentioning
confidence: 99%